2021
DOI: 10.18295/squmj.4.2021.049
|View full text |Cite
|
Sign up to set email alerts
|

Hymenialdisine is Cytotoxic Against Cisplatin-Sensitive but not Against Cisplatin-Resistant Cell Lines

Abstract: New compounds are needed to overcome the resistance to commonly used cytotoxic chemotherapy for epithelial ovarian cancer. Marine sponges are a rich source of diverse chemical compounds, and hymenialdisine has been found to have antiproliferative effects. We investigated the cytotoxic effect of hymenialdisine in cisplatin-sensitive and cisplatin-resistant ovarian cancer cell lines. Methods: The anti-cancer effects of hymenialdisine or cisplatin were assessed by treating cells with different concentrations of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…C-phycocyanin and cisplatin were dissolved in Dulbecco's modified eagle medium (DMEM), respectively. C-phycocyanin solution was further digested with trypsin, and then centrifuged with a 10 kDa ultrafiltration centrifuge tube to obtain C-phycocyanin degradation product; then two solutions over 0.22 μm filter membrane were used to prepare sterile solutions: C-phycocyanin 5 mg/mL (consistent with the concentration of animal experiment) and cisplatin 0.025 mg/mL [1 mg/mL cisplatin solution was obtained at a concentration of 3,333.2 μmol/L ( 19 ). The 48-h IC50 of HepG2 cells is 16 μmol/L ( 20 )].…”
Section: Methodsmentioning
confidence: 99%
“…C-phycocyanin and cisplatin were dissolved in Dulbecco's modified eagle medium (DMEM), respectively. C-phycocyanin solution was further digested with trypsin, and then centrifuged with a 10 kDa ultrafiltration centrifuge tube to obtain C-phycocyanin degradation product; then two solutions over 0.22 μm filter membrane were used to prepare sterile solutions: C-phycocyanin 5 mg/mL (consistent with the concentration of animal experiment) and cisplatin 0.025 mg/mL [1 mg/mL cisplatin solution was obtained at a concentration of 3,333.2 μmol/L ( 19 ). The 48-h IC50 of HepG2 cells is 16 μmol/L ( 20 )].…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 175-177 and 179 showed in vitro cytotoxic capacity against NSCLC-N6 (IC 50 s ranging from 4.8 to 11.2 µg/mL) [66]. In 2021, Abdullah et al reported that 185 was less toxic versus A2780S cells (IC 50 of 146.8 µM) and had no activity versus A2780CP compared to cisplatin (IC 50 of 31.4 µM for A2780S and 76.9 µM for A2780CP) in an alamarBlue ® assay [82]. The guanidine-containing alkaloids 191-193 were evaluated for the cellular stability of PDCD4 (Programmed cell death 4) using HEK-293 cells [24].…”
Section: Cytotoxic Activitymentioning
confidence: 99%